Study on Electrochemical and Antiknock Properties of Toluidine - Jin, Ming; Yu, Zhangyu (Asian Journal of Chemistry, 2011)
Aromatic amine is an additive in gasoline, preventing gasoline from knocking combustion. Mechanism of toluidines function was studied on the basis of electrochemical properties of o-, m- and p-toluidines and their interaction with hydrogen peroxide. The electrochemical properties and the interaction were investigated by cyclic voltammetry and in situ UV-VIS spectroelectrochemistry. Experimental results indicated that low parent concentration and nonprotonic solvent are in favour of producing dimers and/or short oligomers for the toluidines. Antiknock properties of the toluidines are related essentially to deprotonation existing in the formation of their dimers and to positioning of the ring substituent. The paper presents significant information on antiknock properties of toluidines using an electrochemical method.